2009
DOI: 10.1519/jsc.0b013e3181bcd5fe
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Performance Comparisons in Professional Baseball Players

Abstract: This study compared anthropometric and performance variables in professional baseball players and examined the relationship between these variables and baseball-specific performance (i.e., home runs, total bases, slugging percentage, and stolen bases). During a 2-year period, 343 professional baseball players were assessed for height, weight, body composition, grip strength, vertical jump power, 10-yard sprint speed, and agility. Subject population consisted of players on the rosters of one of the minor league… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 7 publications
3
48
2
Order By: Relevance
“…The present investigation has contrasting findings to other studies investigating lower-body power output and on field performance in baseball athletes. 11 While the correlation coefficients investigations are similar (low to moderate), the present study did not reach statistical significance, unlike the previous investigations. This can be a result of the difference in the variables used as those of previous studies involved offensive statistics (home runs, runs batted in, batting average, etc) over the course of the season, whereas this investigation looked at pitching velocity using a cross-sectional design.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The present investigation has contrasting findings to other studies investigating lower-body power output and on field performance in baseball athletes. 11 While the correlation coefficients investigations are similar (low to moderate), the present study did not reach statistical significance, unlike the previous investigations. This can be a result of the difference in the variables used as those of previous studies involved offensive statistics (home runs, runs batted in, batting average, etc) over the course of the season, whereas this investigation looked at pitching velocity using a cross-sectional design.…”
Section: Discussioncontrasting
confidence: 87%
“…9 The vertical jump, as well as throwing velocities and body composition have been suggested as a method in measuring fatigue over the course of a season. 10 Furthermore, lower body power assessed through the vertical jump has been shown to have a positive relationship on offense 11 and fielding 12 performance over the course of a season in professional baseball players. Based on the body of research, there is an expectation that lower body power and force production is significantly associated with pitching velocity in professional pitchers.…”
Section: Introductionmentioning
confidence: 99%
“…17 Jump height was used as a relative measure of power and measured consistently across all subjects. 11,12,14,15 …”
Section: Methodsmentioning
confidence: 99%
“…Dominant and non-dominant HGS differences observed in tennis athletes might be caused by asymmetrical trainings in tennis [8]. In studies to find out the correlation between HGS and performance, it was reported that HGS and performance of the athletes are positively related [14,15].…”
Section: Introductionmentioning
confidence: 99%